Metaphilosophical profiles: No. 7(2020) - Kleszcz, Ryszard (Lodz University Press, 2020)
The monograph is a work in the field of philosophy and concerns its section called metaphilosophy, which studies the nature, methods, tasks, goals, subject and scope of philosophical research. The point of reference for metaphilosophical considerations are the metaphilosophical views of the most eminent representatives of the most important Polish philosophical school in the twentieth century, i.e. the Lvov-Warsaw School, founded at the end of the 19th century by Kazimierz Twardowski. They were supplemented and contrasted with the views of other prominent Polish philosophers of the 20th century, such as Henryk Elzenberg and Bogusław Wolniewicz.